Effect of Multi-Source Ultrasonic on the Microstructure and Mechanical Properties of a Large Scale 2219 Al Alloy Ingot During Casting - Li, Anqing; Jiang, Ripeng; Liu, Zhilin; Li, Ruiqing; Zhang, Yun (Frontiers in Materials, 2022)
Usage of high-energy ultrasonic vibration is an effective approach that can dramatically improve the performance of large-scale ingots. In this work, it was applied to manufacture large 2219 aluminum alloy ingots (630 mm in diameter and 4,500 mm in length). The degassing efficiency, the average size of α-Al grains, the morphology of the Al2Cu phase under double-source ultrasound (DSU), and three-source ultrasound (TSU) were compared. Meanwhile, the influence of the ultrasonic field on the macroscopic segregation of the Cu content and mechanical properties was scientifically investigated. It was found that the degassing efficiency of TSU was significantly higher than that of DSU. The results also indicated that α-Al grains were effectively refined under the TSU technology from the center to the edge of the ingot. Additionally, the distribution of the macroscopic Cu content was more uniform, and the area fraction of the Al2Cu phase was evidently decreased. The mechanical properties of the ingot were superior to samples with DSU technology. Furthermore, it was demonstrated that the stress concentration of the coarse Al2Cu phase at the center of the DSU process led to the deterioration of the mechanical properties.